2013
DOI: 10.1177/1352458512472747
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Nintendo® Wii® on balance in people with multiple sclerosis: a pilot randomized control study

Abstract: Improvement of sensory strategies is a relevant part of balance rehabilitation in multiple sclerosis (MS). This study aimed to Assess the effectiveness of visual-feedback exercises in improving balance in MS. We divided 36 patients into Wii and control-treated groups that underwent balance rehabilitation. Outcomes were obtained for Berg Balance Scale (BBS), Modified Fatigue Impact Scale, and sway area under conditions of opened and closed eyes. BBS showed a statistically significant improvement (from 49.6 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 9 publications
10
107
0
7
Order By: Relevance
“…51,52 Karim et al showed that playing exergames resulted in a robust hyperemic response in the superior temporal gryus and supramarginal gyrus, 51 indicating that these areas were important for balance. Furthermore, the duration of this response after cessation was prolonged (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) s longer than what would be expected), suggesting an adaptation of the vestibular network in response to the balance task. After 12-weeks of Wii balance training, Prosperini et al showed an improvement in balance, 52 suggesting a functional restoration (i.e.…”
Section: Participant's Experience Of Exergamingmentioning
confidence: 80%
“…51,52 Karim et al showed that playing exergames resulted in a robust hyperemic response in the superior temporal gryus and supramarginal gyrus, 51 indicating that these areas were important for balance. Furthermore, the duration of this response after cessation was prolonged (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) s longer than what would be expected), suggesting an adaptation of the vestibular network in response to the balance task. After 12-weeks of Wii balance training, Prosperini et al showed an improvement in balance, 52 suggesting a functional restoration (i.e.…”
Section: Participant's Experience Of Exergamingmentioning
confidence: 80%
“…Reducing fall risk has been reported both in studies for people with Parkinson Disease (PD) 26 and people with Multiple Sclerosis (MS). 27 There is work with active video games for wellness fitness for prevention.…”
Section: Preventionmentioning
confidence: 99%
“…The inclusion criteria varied considerably between the studies. All studies included participants with de initively diagnosed MS, but only 5 studies required the diagnosis to be de ined in accordance with the McDonald criteria, [33][34][35][36]12]. Nine studies included either a partial or complete breakdown of the subtypes of MS, which identi ied Relapse-Remitting Multiple Sclerosis (RRMS) as the leading sub-type; (RRMS n=425 (85.5% of reported MS sub-type), Primary Progressive MS (PPMS) n=22, Secondary Progressive MS (SPMS) n= 50, Unknown n=221).…”
Section: Considering the Summary Of Included Studiesmentioning
confidence: 99%